Предмет: Алгебра,
автор: 1ll1
8m-n/mn-m^2 - m-8n/mn-n^2
Ответы
Автор ответа:
0
(8m - n)/(mn - m²) - (m - 8n)/(mn - n²) = (8m - n)(mn - n²)/(mn - m²)(mn - n²) - (m -
- 8n)(mn - m²)/(mn - m²)(mn - n²) = ((8m - n)(mn - n²)-(m - 8n)(mn - m²))/(mn - m²)(mn - n²) = (8m²n - 8mn² - mn² + n³ - (m²n-m³ - 8mn² + 8nm²))/(mn - m²)(mn - n²) =
= (8m²n - 8mn² - mn² + n³ - m²n + m³ + 8mn² - 8nm²)/(mn - m²)(mn - n²) = (n³ -
- mn² - m²n + m³)/(m²n² - m³n - mn³ + m²n²) = (n³ - mn² - m²n + m³)/nm((-m²) + mn
+ mn - n²) = (n³ - mn² - m²n + m³)/(-nm)(m² - 2mn + n²)
- 8n)(mn - m²)/(mn - m²)(mn - n²) = ((8m - n)(mn - n²)-(m - 8n)(mn - m²))/(mn - m²)(mn - n²) = (8m²n - 8mn² - mn² + n³ - (m²n-m³ - 8mn² + 8nm²))/(mn - m²)(mn - n²) =
= (8m²n - 8mn² - mn² + n³ - m²n + m³ + 8mn² - 8nm²)/(mn - m²)(mn - n²) = (n³ -
- mn² - m²n + m³)/(m²n² - m³n - mn³ + m²n²) = (n³ - mn² - m²n + m³)/nm((-m²) + mn
+ mn - n²) = (n³ - mn² - m²n + m³)/(-nm)(m² - 2mn + n²)
Похожие вопросы
Предмет: Математика,
автор: titovaa333
Предмет: История,
автор: debdebovis
Предмет: Русский язык,
автор: daniks02032011
Предмет: Математика,
автор: 000AREA000
Предмет: Геометрия,
автор: Аноним